Association of markers of endothelial activation and dysfunction with occurrence and outcome of pulmonary hemorrhage in dogs with leptospirosis. (2nd June 2021) - Sonderegger, Franziska; Nentwig, Alice; Schweighauser, Ariane; Francey, Thierry; Marti, Eliane; Mirkovitch, Jelena; Schuller, Simone
Abstract: Background: Endothelial dysfunction might contribute to the development of leptospiral pulmonary hemorrhage syndrome (LPHS). Hypothesis: Serum concentrations of markers of endothelial activation and dysfunction are higher in dogs with leptospirosis and correlate with the occurrence of LPHS and a higher case fatality rate. Animals: Clinically healthy dogs (n = 31; 10/31 dogs confirmed healthy based on no detected abnormalities on blood work), dogs with leptospirosis with LPHS (n = 17) and without LPHS (n = 15), dogs with acute kidney injury not due to leptospirosis (AKI‐nL, n = 34). Methods: Observational study. Serum concentrations of soluble intercellular adhesion molecule 1 (sICAM‐1), vascular endothelial growth factor (VEGF), and angiopoietin‐2 (Ang‐2) at admission were compared between groups. Correlations with outcome and the accuracy to predict LPHS were examined. Results: Soluble intercellular adhesion molecule (sICAM‐1), VEGF, and Ang‐2 concentrations were higher in dogs with AKI‐nL (sICAM‐1 34.7 ng/mL, interquartile range [IQR] = 24.4‐75.5; VEGF 43.1 pg/mL, IQR = 12.3‐79.2; Ang‐2 8.5 ng/mL, IQR = 6.2‐12.3), leptospirosis without LPHS (sICAM‐1 45.1 ng/mL, IQR = 30.6‐59.0; VEGF 32.4 pg/mL, IQR = 12.5‐62.6; Ang‐2 9.6 ng/mL, IQR = 6.9‐19.3), and LPHS (sICAM‐1 69.7 ng/mL, IQR = 42.1‐89.1; VEGF 51.8 pg/mL, IQR = 26.3‐96.7; Ang‐2 8.0 ng/mL, IQR = 5.6‐12.2) compared to controls ( P  < .001). In dogs with leptospirosis, VEGF and sICAM‐1 were higher in nonsurvivors (sICAM‐1 89.4 ng/mL, IQR = 76.5‐101.0; VEGF 117.0 pg/mL, IQR = 90.3‐232.4) than survivors ( P  = .004) and sICAM‐1 predicted the development of LPHS. Conclusions: Soluble intercellular adhesion molecule 1, VEGF, and Ang‐2 do not discriminate leptospirosis from AKI‐nL. In dogs with leptospirosis, sICAM‐1 and VEGF predict outcome and sICAM‐1 might identify dogs at risk for LPHS.